Prostaglandin E1 attenuates AngII-induced cardiac hypertrophy via EP3 receptor activation and Netrin-1upregulation. (14th October 2021) - Shen, L; Shen, Y; Wang, X; He, B
Abstract: Aims: Pathological cardiac hypertrophy induced by activation of the renin–angiotensin–aldosterone system (RAAS) is one of the leading causes of heart failure. However, in current clinical practice, the strategy for targeting the RAAS is not sufficient to reverse hypertrophy. Here, we investigated the effect of prostaglandin E1 (PGE1) on angiotensin II (AngII)-induced cardiac hypertrophy and potential molecular mechanisms underlying the effect. Methods and results: Adult male C57 mice were continuously infused with AngII or saline and treated daily with PGE1 or vehicle for two weeks. Neonatal rat cardiomyocytes were cultured to detect AngII-induced hypertrophic responses. We found that PGE1 ameliorated AngII-induced cardiac hypertrophy both in vivo and in vitro. The RNA sequencing (RNA-seq) and expression pattern analysis results suggest that Netrin-1 (Ntn1) is the specific target gene of PGE1. The protective effect of PGE1 was eliminated after knockdown of Ntn1. Moreover, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the PGE1-mediated signaling pathway changes are associated with the mitogen-activated protein kinase (MAPK) pathway. PGE1 suppressed AngII-induced activation of the MAPK signaling pathway, and such an effect was attenuated by Ntn1 knockdown. Blockade of MAPK signaling rescued the phenotype of cardiomyocytes caused by Ntn1 knockdown, indicating that MAPK signaling may act as the downstream effector of Ntn1. Furthermore, inhibition of the E prostanoid (EP)3 receptor, as opposed to the EP1, EP2, or EP4 receptor, in cardiomyocytes reversed the effect of PGE1, and activation of EP3 by sulprostone, a specific agonist, mimicked the effect of PGE1. Conclusion: In conclusion, PGE1 ameliorates AngII-induced cardiac hypertrophy through activation of the EP3 receptor and upregulation of Ntn1, which inhibits the downstream MAPK signaling pathway. Thus, targeting EP3, as well as the Ntn1–MAPK axis, may represent a novel approach for treating pathological cardiac hypertrophy. FUNDunding Acknowledgement: Type of funding sources: None.